2006
DOI: 10.1128/iai.01262-05
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofBurkholderia pseudomalleiGenes Required for the Intracellular Life Cycle and In Vivo Virulence

Abstract: The bacterial pathogen Burkholderia pseudomallei invades host cells, escapes from endocytic vesicles, multiplies intracellularly, and induces the formation of actin tails and membrane protrusions, leading to direct cell-to-cell spreading. This study was aimed at the identification of B. pseudomallei genes responsible for the different steps of this intracellular life cycle. B. pseudomallei transposon mutants were screened for a reduced ability to form plaques on PtK2 cell monolayers as a result of reduced inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
193
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(204 citation statements)
references
References 48 publications
10
193
1
Order By: Relevance
“…BPSS1509 corresponds to the tssK orthologue in the macrophage-inducible tss-5 unit. Our observation that inactivation of tssH-5 does not significantly affect the ability of B. pseudomallei to survive in macrophages is in agreement with the observation of Pilatz et al (2006) regarding the normal growth phenotype of the tssK-5 mutant in macrophages. Moreover, in the three co-integrate strains that we isolated in which pGSTp was integrated in the tss-5 unit, it is likely that expression of the tss genes located downstream of the integrated vector were also disrupted (as the genomic fragments cloned into pGSTp were too small to contain the predicted promoter region).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…BPSS1509 corresponds to the tssK orthologue in the macrophage-inducible tss-5 unit. Our observation that inactivation of tssH-5 does not significantly affect the ability of B. pseudomallei to survive in macrophages is in agreement with the observation of Pilatz et al (2006) regarding the normal growth phenotype of the tssK-5 mutant in macrophages. Moreover, in the three co-integrate strains that we isolated in which pGSTp was integrated in the tss-5 unit, it is likely that expression of the tss genes located downstream of the integrated vector were also disrupted (as the genomic fragments cloned into pGSTp were too small to contain the predicted promoter region).…”
Section: Discussionsupporting
confidence: 79%
“…2). T3SS-3 has been shown to be important for growth of B. pseudomallei within macrophage-like cells and for escape from endocytic vacuoles, and one of the associated effector proteins, BopE (BPSS1525), is required for efficient invasion of epithelial cells (Stevens et al, 2002(Stevens et al, , 2003Ribot & Ulrich, 2006;Pilatz et al, 2006). T3SS-3 is also required for maximum virulence of B. pseudomallei in murine and hamster models of infection (Stevens et al, 2004;Warawa & Woods, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Pilatz et al demonstrated that a mutant with an insertion in BPSL2825 was severely attenuated in the i.n. BALB/c mouse model; this mutant was also shown to have a defect in iron acquisition and a reduced ability to grow intracellularly (31). In total, putative auxotrophs of five different compounds were identified during this study.…”
Section: Discussionmentioning
confidence: 99%